Infralimbic-basolateral amygdala circuit associated with depression-like not anxiety-like behaviors induced by chronic neuropathic pain and the antidepressant effects of electroacupuncture - Yiping Xie; Zui Shen; Xixiao Zhu; Yushuang Pan; Haiju Sun; Mengdi Xie; Qiuzhu Gong; Qunqi Hu; Jie Chen; Zemin Wu; Shuting Zhou; Boyu Liu; et al. (Brain Research Bulletin)
Chronic pain, such as neuropathic pain, can lead to anxiety, depression, and other negative emotions, thereby forming comorbidities and increasing the risk of chronic pain over time. Both the infralimbic amygdala (IL) and the basolateral amygdala (BLA) are significantly associated with negative emotions and pain, and they are known to have reciprocal connections. However, the role of IL-BLA circuit pathways in neuropathic pain-induced anxiety and depression remains unexplored. Electroacupuncture (EA) is frequently employed in the treatment of chronic pain and emotional disorders. However, The mechanism by which EA mediates its analgesic and emotion-alleviating effects via the IL-BLA circuit remains uncertain. Here, we used chemogenetic manipulation combined with behavioral tests to detect pain induced anxiety-like and depression-like behaviors. We observed that activation of the IL-BLA circuit by chemogenetic activation induced depression-like behavior of mice. Additionally, we discovered that chemogenetic activation of the IL-BLA circuit successfully prevented the beneficial effects of EA on depression-like behavior brought on by chronic pain in mice with spared nerve injury (SNI). We discovered that SNI-induced depression-like behavior could be mitigated by inhibiting the circuit, and EA had a comparable depressive-relieving effect. Furthermore, the IL-BLA circuit's activation or inhibition had no effect on the anxiety-like feelings brought on by SNI. Overall, our findings identify a specific neural circuit that selectively regulates pain-induced depression-like emotions, without affecting pain-induced anxiety-like emotions. This discovery offers a precise target for future treatments of comorbid pain and depression and provides a plausible explanation for the efficacy of EA in treating depression-like emotions associated with chronic pain.